Education, industry and technology - Waddington, D. J.; Steward, J. W. (John William), 1944- (Science and technology education and future human needs ;, 1987)
Education, Industry and Technology is a result of a conference in Bangalore, which discusses industrial and technological issues in primary school science and other related topics. This text specifically examines building applications into secondary science curricula and strategies for teaching science, including the use of games and simulations, work experience programs, industrial visits, and methods of promoting technology as the means for solving problems. The needs of industry and the role of tertiary institutions in development are also some of the highlights of this text. This book will.